2022
DOI: 10.3389/fpsyt.2022.892442
|View full text |Cite
|
Sign up to set email alerts
|

Trait Anxiety Mediates Impulsivity and Suicidal Ideation in Depression During COVID-19 Pandemic

Abstract: Suicidality in patients with major depressive disorder (MDD) has been an urgent affair during the COVID-19 pandemic. It is well-established that impulsivity and trait anxiety are two risk factors for suicidal ideation. However, literature is still insufficient on the relationships among impulsivity, (state/trait) anxiety and suicidal ideation in individuals with MDD. The present study aims to explore the relationships of these three variables in MDD patients during the COVID-19 pandemic through three scales, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…This first finding is consistent with those obtained from other studies, for example, that mood disorders are highly associated with suicide, especially in patients with major depression [1][2][3][4]42]. Our data agree with findings where the presence of clinically significant depression is related to the presence of suicidal ideation [5], and that depressive symptoms increase the likelihood of reflecting suicidal ideation [22][23][24]. Our data also coincide with those found in depressive patients in France, with high levels of anxiety, insomnia, suicidal ideation, and traumatic stress [21].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This first finding is consistent with those obtained from other studies, for example, that mood disorders are highly associated with suicide, especially in patients with major depression [1][2][3][4]42]. Our data agree with findings where the presence of clinically significant depression is related to the presence of suicidal ideation [5], and that depressive symptoms increase the likelihood of reflecting suicidal ideation [22][23][24]. Our data also coincide with those found in depressive patients in France, with high levels of anxiety, insomnia, suicidal ideation, and traumatic stress [21].…”
Section: Discussionsupporting
confidence: 93%
“…In France, loneliness and boredom were independent predictors of depression, anxiety and insomnia in vulnerable people, whereas daily physical activity was a protective factor; virtual contacts also protected against suicidal ideation [21]. In Shanghai, during the COVID-19 pandemic, it was found that, in patients with major depressive disorder, trait anxiety could significantly mediate the relationship between impulsivity and suicidal ideation [22].…”
Section: Introductionmentioning
confidence: 99%
“…Students who showed higher trait anxiety were found to express more negative emotions and to perceive themselves as having less academic self-efficacy [ 38 ]. Patients with major depression who exhibited stronger suicidal ideation were reported to have higher impulsivity and trait anxiety [ 39 ]. The present longitudinal study further suggests the potential of trait anxiety as an easily evaluated predictor of the trajectory of psychological distress in response to stressors.…”
Section: Discussionmentioning
confidence: 99%
“…The SIOSS is a self-rating scale evaluating suicide ideation (Cheng et al, 2022 ; Xia et al, 2012 ). It comprises 26 items divided into 4 dimensions: optimism, sleep, despair, and concealment.…”
Section: Methodsmentioning
confidence: 99%